2022
DOI: 10.1002/cdq.12301
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how aging experiences shape late career development

Abstract: Mature workers’ aging experiences are central in transforming the self and as such can shape career‐related outcomes, such as late career work engagement and motivation to continue working. We therefore investigate the relations between aging experiences (i.e., personal growth, gaining self‐knowledge, social loss, and physical loss) and career‐related outcomes. Moreover, we explore psychological capital as an adaptive set of resources that can explain how aging experiences are linked to mature workers’ motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Future studies could consider university students from different geographical areas in Italy, and from other international contexts. In addition, future research could be addressed to different participants, such as adult workers [86], older individuals [87] and vulnerable workers [88]. Moreover, additional studies could also refine the psychometric properties of the scale using Item Response Theory Models, which could help reduce the number of items [89,90] for a shorter version of the scale.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies could consider university students from different geographical areas in Italy, and from other international contexts. In addition, future research could be addressed to different participants, such as adult workers [86], older individuals [87] and vulnerable workers [88]. Moreover, additional studies could also refine the psychometric properties of the scale using Item Response Theory Models, which could help reduce the number of items [89,90] for a shorter version of the scale.…”
Section: Discussionmentioning
confidence: 99%
“…While these findings seem to support stereotypical views that technology is less popular with increasing age (e.g., Mariano et al, 2020; see also Posthuma & Campion, 2009), the processes behind these findings remain unknown. From the aging literature, we know that there are substantial differences within the group of younger and older employees depending on how employees experience their aging (Fasbender et al, 2019(Fasbender et al, , 2022Kunze et al, 2015;Nagy et al, 2019). For example, research from Drazic and Schermuly (2021) found that age is not per se related to readiness for change but depends on employees' subjective experience of age.…”
Section: Getting Ready For the Future Is It Worth It? A Dual Pathway ...mentioning
confidence: 99%
“…The condition of the Covid-19 pandemic has also affected changes in the work system, causing reduced work motivation, making students who have just graduated less able to take advantage of job opportunities, and resulting in students needing to understand the essence of a career. Junior high school students must have career understanding because it will make a person more careful in matching abilities with work and be a supporting asset for career success (Fasbender et al, 2022;Rosvall, 2020;Salonen, 2020;Spurk & Straub, 2020). However, students need more career awareness from the salary description or job desk (Santi Selviana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%